RANCANG BANGUN SISTEM INFORMASI PENGARSIPAN SURAT PADA DINAS PARIWISATA KOTA PALOPO BERBASIS WEBSITE - Asnur Asnur; Nirsal Nirsal; Syafriadi Syafriadi (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to produce a letter filing information system at the Palopo City Tourism Office based on a website so as to make it easier for agencies to manage mail archive data. The data collection methods used in this research are observation, interviews, documentation and literature studies. In the development of the system, the author uses the Research and Development  method which refers to the Waterfall model. System design using a Unified Modeling Language (UML) approach, while creating a website using PHP, Bootstrap, CSS, Java script  programming languages using MySQL databases. The assessment technique carried out in this system is Blackbox testing. The results of this study are the existence of a website-based mail guarantee information system  that can make it easier for agencies to process mail archive data